Beyond sweatshops : foreign direct investment and globalization in developing countries - Moran, Theodore H., 1943- (Brookings Institution Press, 2002)
"In Beyond Sweatshops, Theodore Moran shows how the dangers associated with FDI can be avoided and the globalization process turned into a win-win outcome for workers and communities in both developed and developing countries." "Moran begins his analysis by examining the perils and the benefits of FDI in export-oriented, labor-intensive industries where sweatshop-type conditions frequently occur. He contrasts plants that have poor working conditions, health and safety violations, and physical and sexual abuse with those that provide worker training, teamwork production, employee promotions, good working conditions, and even health and daycare benefits." "Using export processing zones (EPZs) in the Philippines, the Dominican Republic, and Costa Rica as examples, Moran shows that the movement from low-skilled activities to slightly higher skilled operations is the key to improving worker treatment in the developing world. Through his examination of the automotive, computer, and electronics industries in Latin America and Southeast Asia, Moran illustrates the way FDI can transform the overall development profile of an entire host country - redefining the economic prospects of hundreds of thousands of workers who are not directly employed in foreign plants. He presents evidence that the greatest flows of FDI are not directed toward lowest-skilled occupations, but go instead to sectors that pay production workers five times more than what is found in garment, textile, and footwear plants."--Jacket